DAMPAK PERNIKAHAN DINI TERHADAP KEHARMONISAN KELUARGA DAN POLA ASUH ANAK (Studi Kasus Atas Masyarakat Desa Sukaraja Lampung Timur) - Heri Cahyono; Eka Dewi (Universitas Muhammadiyah Metro, 2018)
Early marriage affects the formation of a family that is not harmonious. That is because psychologically and socio-economically the early marriage partner is not yet mature. They are classified as unstable and generally do not have a permanent job. Besides being unstable, early marriage partners also do not have much knowledge about how to care for children, so they cannot apply the right pattern of parenting.The hypothesis in this study is that there is the effect of early marriage on Family Harmony in the village of Sukaraja Tiga, Kec. Marga Tiga, Kab. East Lampung and there is an influence of early marriage on the pattern of child care in the village of Sukaraja Tiga, Kec. Marga Tiga, Kab. East Lampung. This study is a population study with a population of 15 early marriage partners. Data analysis in this study uses the Product Moment formula.The results showed that the first hypothesis was accepted, as evidenced by the price of r_xy 0.573 greater than r_tabel at df = N-nr = 15-2 = 13 and a significance level of 5% at 0.514, so it can be concluded that the theory that